2016
DOI: 10.13005/ojc/320208
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NiW Modified HZSM-5 and HY Zeolites on Hydrocracking Conversion of Crude Palm Oil to Liquid Hydrocarbons

Abstract: The catalytic conversion of crude palm oil over HZSM-5 and HY zeolites modified with NiW as catalysts in the hydrocracking process was investigated. These zeolites supported by NiW catalysts were prepared employing the impregnation technique. NiW was added to the zeolites in order to induce bi-functional properties (both acid and metal sites) in the catalysts. Subsequently, the catalysts were characterized by X-ray diffraction spectrometry (XRD), scanning electron microscope (SEM), transmission electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The XRD patterns of the fresh catalysts were similarity indicating that the framework of HZSM-5 was still kept after loading Zn(II). The ZnO phase was not observed for fresh catalysts suggesting that the metal oxide species were well dispersed on surface of the support HZSM-5 6,13 . The BET surface areas and pore volumes of fresh catalysts are listed in Table 1.…”
Section: Feedstock and Catalyst Characterizationmentioning
confidence: 98%
“…The XRD patterns of the fresh catalysts were similarity indicating that the framework of HZSM-5 was still kept after loading Zn(II). The ZnO phase was not observed for fresh catalysts suggesting that the metal oxide species were well dispersed on surface of the support HZSM-5 6,13 . The BET surface areas and pore volumes of fresh catalysts are listed in Table 1.…”
Section: Feedstock and Catalyst Characterizationmentioning
confidence: 98%
“…The results indicate that the catalyst doped with NiW had a better hydrocracking performance compared to the catalyst that was not metallically modified. [108] The NiW was again used for hydrocracking with NiMo in their sulphided form for a conversion comparative study on Jatropha oil at a temperature of 400 and 425 C. The sulphided NiMo and NiW were in combination with the hierarchical mesoporous SAPO-11 (MSP-1 and MSP-2). Higher temperatures alongside the supports and acidic character were more selective for the kerosene production, due to hydrocracking activity favoured for those conditions.…”
Section: Metal Catalystsmentioning
confidence: 99%
“…15 Various catalysts and hydrotreating reaction conditions using CPO as the feedstock have been reported. Subsadsana and Ruangviriyachai 16 successfully converted CPO to biofuels through hydrocracking using an NiW-modied zeolite-based catalyst and provided high conversion efficiency. Subsadsana et al 17 showed that the hydrocracking of CPO generated the corresponding hydrocracking fractions such as gasoline, kerosene, and diesel catalyzed by NiW-modied ZSM-5 zeolite.…”
Section: Introductionmentioning
confidence: 99%